An Introduction to Groups, Groupoids and Their Representations - Ibort, Alberto; Rodriguez, Miguel A. (Milton : CRC Press LLC, 2019)
This book offers an introduction to the theory of groupoids and their representations encompassing the standard theory of groups. Using a categorical language, developed from simple examples, the theory of finite groupoids is shown to knit neatly with that of groups and their structure as well as that of their representations is described. The book comprises numerous examples and applications, including well-known games and puzzles, databases and physics applications. Key concepts have been presented using only basic notions so that it can be used both by students and researchers interested in the subject.
5.2 An interlude: Categories and databases5.2.1 A simple database: Classes and courses; 5.2.2 Databases and functors; 5.3 Homomorphisms of groupoids; 5.3.1 Homomorphisms of groupoids: Basic notions; 5.3.2 Exact sequences of homomorphisms of groupoids; 5.3.3 Homomorphisms of groupoids, direct unions and products of groupoids; 5.3.4 Groupoids of automorphisms; 5.4 Equivalence: Natural transformations; 5.4.1 Equivalence of categories; 5.4.2 The notion of natural transformation; 6. The Structure of Groupoids; 6.1 Normal subgroupoids; 6.2 Simple groupoids
Description based upon print version of record.
6.3 The structure of groupoids: Second structure theorem
OCLC-licensed vendor bibliographic record.
Keywords: Groupoids; MATHEMATICS / Algebra / General; MATHEMATICS / Geometry / General; MATHEMATICS / Combinatorics